A short form of the neonatal intensive care unit family needs inventory - Elisabete Alves; Milton Severo; Mariana Amorim; Catarina Grande; Susana Silva (Brazilian Society of Pediatrics, 2016)
Objective: The identification of parental needs in Neonatal Intensive Care Units (NICU) is essential to design and implement family‐centered care. This article aims to validate the NICU Family Needs Inventory for the Portuguese population, and to propose a Short Form. Methods: A linguistic adaptation of the NICU Family Needs Inventory, a self‐report scale with 56‐items, was performed. The instrument was administered to 211 parents of infants hospitalized in all level III NICU in the North of Portugal, 15 to 22 days after admission (July of 2013‐June of 2014). The number of items needed to achieve reliability close to 0.8 was calculated using by the Spearman‐Brown formula. The global goodness of fit of the scale was evaluated using the comparative fit index (CFI). Construct validity was assessed through association of each dimension score with socio‐demographic and obstetric characteristics. Results: Exploratory factor analysis revealed two dimensions, one focused on parents' needs and another on the infant's needs. To compose the Short Form Inventory, items with ceiling effect were eliminated and 22 items were submitted to confirmatory analysis, which supported the existence of two dimensions (CFI = 0.925). The Short Form showed a high degree of reliability (alpha ≥ 0.76). Less educated and older parents more frequently attributed a significantly higher importance to parent‐centered needs, while parents of multiples revealed a tendency to value infant‐centered needs. Conclusions: The Short Form of the NICU Family Needs Inventory is a brief, simple, and valid instrument with a high degree of reliability. Further studies are needed to explore associations with practices of family‐centered care.